2002
DOI: 10.1161/01.cir.0000016062.80020.11
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction in Canine Pulmonary Veins

Abstract: Background-Paroxysmal atrial fibrillation in patients is often initiated by foci in the pulmonary veins. The mechanism of these initiating arrhythmias is unknown. The aim of this study was to determine electrophysiological characteristics of canine pulmonary veins that may predispose to initiating arrhythmias. Methods and Results-Extracellular recordings were obtained from the luminal side of 9 pulmonary veins in 6Langendorff-perfused dog hearts after the veins were incised from the severed end to the ostium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
103
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 318 publications
(117 citation statements)
references
References 13 publications
12
103
0
2
Order By: Relevance
“…90,91 One important factor could be the shorter action potential duration (APD) of the PVs vs the atrium 84 due to larger delayed-rectifier K + currents and smaller inward Ca 2+ currents in the PV. 89,92,93 In addition, PVs demonstrate conduction abnormalities that promote reentry due to abrupt changes in fiber orientation as well as Na + channel inactivation by reduced resting potentials due to small I K1 .…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
“…90,91 One important factor could be the shorter action potential duration (APD) of the PVs vs the atrium 84 due to larger delayed-rectifier K + currents and smaller inward Ca 2+ currents in the PV. 89,92,93 In addition, PVs demonstrate conduction abnormalities that promote reentry due to abrupt changes in fiber orientation as well as Na + channel inactivation by reduced resting potentials due to small I K1 .…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%
“…A recent study conducted in dogs reported conduction patterns in PVs similar to those described here. 11 The activation delay was correlated with complex fiber arrangement and particularly with abrupt changes in their direction. These decremental conduction properties could therefore be related to anisotropic conduction, 12 with the fractionated venous potentials and associated changes in activation sequence and exits probably correlating with the complex arrangement of venous muscular sleeves reported by pathologists in humans.…”
Section: Jaïs Et Al Electrophysiological Properties Of Pvs 2483mentioning
confidence: 98%
“…Em cães, os circuitos de micro-reentrada, o automatismo e a atividade trigger têm sido apontados como mecanismos associados a ocorrência de arritmias auriculares 28,29 . Hayashi e colaboradores usaram estimulação vagal cervical para indução de FA com bursts de pacing auricular em cães anestesiados 30 .…”
Section: Modelos Animais E Estudo Da Vulnerabilidade Para Fibrilhaçãounclassified